EGG QUALITY CHARACTERISTICS AS INFLUENCED BY DIFFERENT BODY SIZES IN FOUR CLOSE-BRED FLOCKS OF JAPANESE QUAILS (Coturnix coturnix japonica) - A. S. Jatoi; A. W. Sahota; M. Akram; K. Javed; M. H. Jaspal; S. Mehmood; J. Hussain; H. M. Ishaq; E. Bughio (Journal of Animal and Plant Sciences, 2015)
The present study was conducted to investigate some egg quality traits in four close-bred flocks of adult Japanese quails responded by different body sizes maintained at Avian Research and Training Centre, University of Veterinary and Animal Sciences, Lahore. A total of 432 adult (12 weeks-old) quails, comprising 108 males and 324 females were randomly divided into 108 experimental units, comprising one male and three females each. These experimental units were randomly assigned to 12 treatment groups having 4 close-bred flocks x 3 female body weights (heavy 300-350g, medium 250-300g and small 200-250g) with randomized complete block design in factorial arrangements having 9 replicates in each treatment. Egg weight (g), shell weight (g), shell thickness (mm), haugh unit, yolk index and blood and meat spots were studied. The significant (p<0.05) differences were noted in mean egg weight, shell weight, shell thickness and yolk index, whereas, haugh unit value was not significantly different in all the close-bred flocks of Japanese quails. With respect to body size categories, differences for egg weight, shell weight, shell thickness, yolk index and haugh unit value were significant (p<0.05). The interaction between flocks and body size was significant (p<0.05) in respect of all the above egg quality traits. The egg weight was higher in imported flock than local-1 and local-2 flocks and egg shell weight was higher in imported flock than in other local flocks. However, egg shell thickness and haugh unit were found to be higher in local-2 than local-1, 3 and imported flocks. The heavy weight quails had maximum egg weight, egg shell weight, shell thickness and yolk index followed by those in the medium and small size groups. Blood and meat spots were not observed during the course of this study.
Keywords: Japanese quails; egg weight; shell weight; shell thickness; haugh unit; yolk index and blood and meat spots